Scalable synthesis of Ca-doped α-Fe₂O₃ with abundant oxygen vacancies for enhanced degradation of organic pollutants through peroxymonosulfate activation - Guo, Sheng (2022)
In this work, a cost-effective and eco-friendly calcium-doped α-Fe2O3 (Ca-Fe2O3) with abundant oxygen vacancies was fabricated using a scalable precipitation-calcination method to activate peroxymonosulfate (PMS) for wastewater purification. Density functional theory calculations revealed that the incorporation of Ca2+ into the α-Fe2O3 structure enhances the electron transfer from α-Fe2O3 to PMS, facilitating the activation of PMS. The degradation of Rhodamine B by 5%Ca-Fe2O3 proceeded with a reaction constant 8 times higher than that of pristine α-Fe2O3. This can be attributed to the increased generation of 1O2 and O2•−, increased specific surface area and enhanced electrical conductivity. The applicability of the 5%Ca-Fe2O3/PMS system was investigated including its operating parameters and stability, and the intermediates involved in the reaction were identified. The 5%Ca-Fe2O3/PMS system exhibited excellent degradation efficiency in natural water samples. This work opens up new perspectives for designing highly efficient catalysts and renders iron oxides potential candidates for environmental remediation.